2013
DOI: 10.5858/arpa.2012-0297-oa
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Upgrade Rates on Subsequent Excision When Lobular Carcinoma In Situ Is the Primary Diagnosis in the Needle Core Biopsy With Special Attention to the Radiographic Target

Abstract: Context.—Lobular carcinoma in situ (LCIS) as the primary pathologic diagnosis in a needle core biopsy is an infrequent finding, and the management of patients in this setting is controversial. Objective.—To determine the rate of pathologic upgrade (defined as the presence of a clinically more-significant lesion in the subsequent excision) in patients with a primary pathologic diagnosis of LCIS in the needle core biopsy. Design.—Patients with a primary diagnosis of LCIS in a needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…The upgrade rate after classical LN diagnosis on CB or VAB is variable in the literature, ranging from 0 to 50 % which can at least partially be explained by variation in study design and inconsistent use of ALH, LCIS, and LN nomenclatures [2, 41]. In one study, underestimation was found to be 4 % in classical LN cases when LN was an incidental finding and 18 %, when LN represented the radiologic targets by D’Alfonso et al [50]. Higher upgrade rates were associated with cases that demonstrated mass lesions and calcification on imaging or with radiopathological discordance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upgrade rate after classical LN diagnosis on CB or VAB is variable in the literature, ranging from 0 to 50 % which can at least partially be explained by variation in study design and inconsistent use of ALH, LCIS, and LN nomenclatures [2, 41]. In one study, underestimation was found to be 4 % in classical LN cases when LN was an incidental finding and 18 %, when LN represented the radiologic targets by D’Alfonso et al [50]. Higher upgrade rates were associated with cases that demonstrated mass lesions and calcification on imaging or with radiopathological discordance.…”
Section: Resultsmentioning
confidence: 99%
“…Higher upgrade rates were associated with cases that demonstrated mass lesions and calcification on imaging or with radiopathological discordance. Lower underestimation rates were detected in classical LN cases, where no residual calcification was found after biopsy, calcification was incidental, and there was complete concordance between histological and imaging findings [2, 41, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…However, the radiology-pathology correlation data are either missing or incomplete in many studies. 4 Studies that have included radiology-pathology correlation for core biopsy cases with papillomas 22,23 and lobular neoplasia [24][25][26] tend to report lower upgrade rates and may argue against mandatory excision for these diagnoses on core biopsy. Similarly, our overall upgrade rate of 7% for cases with careful correlation is lower than the majority of published studies with 30 or more excisions (Table 4) and closer to the 9.5% reported by Bianchi et al 27 in a series of 589 cases from multiple hospitals in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it seems prudent to offer excision to patients with a core biopsy diagnosis of flat epithelial atypia with limited sampling of the radiographic target or discordant imaging findings, similar to what has been proposed for solitary papillomas and lobular neoplasia diagnosed on core biopsy. [24][25][26] Most studies evaluating the upgrade rates of flat epithelial atypia on core biopsy have not reported the characteristics of the carcinoma upgrades identified on excision. As this study demonstrates, flat epithelial atypia is associated with other forms of low-grade atypia and low-grade estrogen receptorpositive carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…6,19,41,61,[66][67][68][69] As expected, many studies include few patients, including some with fewer than 5 patients. 52,64,70,71 A meta-analysis by Pieri et al 68 that included 42 patients with pleomorphic LCIS on core biopsy from 5 studies showed an upgrade rate of 36% (15 of 42; 14 invasive carcinomas, 1 DCIS). Most upgraded lesions in these studies were invasive lobular carcinomas, which were seen in close proximity to the florid or pleomorphic LCIS.…”
Section: Pathologic Upgrade and Surgical Management After Diagnosis Omentioning
confidence: 99%